"COURAGE OF UZBEK PEOPLE IN THE BATTLE ON THE THRESHOLD OF STALINGRAD" (Archive of Conferences, 2021)
This article is about the history of the Soviet era, the history of the Soviet era, the history of the Soviet Union, the history of the Soviet Union, the history of the Soviet Union, the history of the Soviet Union, the history of the Soviet Union, the history of the Soviet Union. and the feeling of glorification and protection, the devotion on this path, the great courage of the Uzbek heroes, who mobilized all their energy in the cause of peace, the noble and lofty goal.